Kepuasan kerja: kajian di kalangan pensyarah di Akademi Pengajian Islam dan Fakulti Bahasa dan Linguistik Universiti Malaya - Azmi, I.A.G. (2005)
This study examines the level of job satisfaction among the lecturers of Academy of Islamic Studies and Faculty of Language and Linguistics, identifies the motivator, hygiene and demographic factors that influence the level of respondents' job satisfaction, their plans, preparation and reasons in choosing this profession as their career, the potential and reasons to turnover intention, the actions to be taken by them given their level of job satisfaction and their suggestions to remedy. It's found that the overall job stafisfaction in both faculties is high i.e.77.3% at Academy of Islamic Studies and 78.8% at Faculty of Language and Linguistics.